Political and social networks in Tajikistan and Uzbekistan: 'Clan', region and beyond - (:unkn) unknown (My University, 2009)
A major debate among scholars studying Central Asian societies concerns the structure of social and political networks in the region. Still unresolved is the issue of whether to define such networks in terms of 'clans', 'regionalism', or personal networks. This article, based on data collected during fieldwork in Tajikistan and Uzbekistan, attempts to understand these social and political networks. It suggests that networks are very complex. The networks in Tajikistan and Uzbekistan draw on various loyalties including ties of family, friendship, work, education, and patron-client relationships. They are neither purely regional nor purely clan-based. Personal networks, factions, and self-interest play important roles. At the elite level, networks more closely resemble patron-client networks, which may or may not include regional or kinship ties. Among ordinary people, such ties tend to be based on localism, kinship, and/or patronage relationships. © 2009 Central Asian.
Keywords: Central Asia; Clan; Patron-client networks; Regionalism; Tajikistan; Uzbekistan